Pengaruh Market Value Added (MVA), Net Profit Margin (NPM) dan Return On Equity (ROE) Terhadap Harga Saham Pada Perusahaan Telekomunikasi Yang terdaftar di BEI - Suhatina, Suhatina; Amani, Tatik; Priantono, Seger (Universitas Panca Marga, 2024)
This research aims to examine the influence of Market Value Added (MVA), Net Profit Margin (NPM) and Return On Equity (ROE) on share price in telecommunications companies listed on the Indonesia Stock Exchange. The type of research used is quantitative, with the independent variables Market Value Added (MVA), Net Profit Margin and Return On Equity (ROE). Meanwhile, the dependent variable used is share price. The population of this research is the telecommunications companies listed on the Indonesia Stock Exchange. Sample selection was carried out using purposive sampling technique. The selected sample was 20 companies. The analytical method used include the classical assumption test, multiple linear regression analysis test, coefficient of determination, t- test, F-test and dominant test. The results of hypothesis testing show that partially Market Value Added (MVA), and Return On Equity (ROE) have a positive and significant effect on share price, while the Net Profit Margin (NPM) have a negative and insignificant effect on share price. Simultaneously Market Value Added (MVA), Net Profit Margin (NPM) dan Return On Equity (ROE) have a simultaneously effect on share price. Market Value Added (MVA) have a dominant influence on share price.